Test suite reduction and prioritization framework in regression testing - Musa, Samaila; Md Sultan, Abu Bakar (Science Research Society, 2021)
Most of the test cases minimization reduced test cases during regression testing to generate new test suite to cover the same software requirements. The objective of this paper is to present new framework that integrate the idea of minimization and prioritization. Hence, reduction and prioritization able to reduce test cases based on the statements covered by the previous test cases to avoid redundancy. Beginning from the reduction of the test cases, followed by weighted prioritization according to their usefulness. The framework was tested using sample test suite and the results obtained shown increases on the average percentage of faults detection (APFD). Future plan is to test on the larger size of test suite.